2015
DOI: 10.22495/jgr_v4_i1_p1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of corporate social responsibility on brand loyalty.

Abstract: This article describes corporate social responsibility (CSR) as an organisational tool whose successful implementation can be used to gain brand loyalty. The benefits of CSR to society have been well documented to a great extent. However, there is very little information on the benefits of it to the actual corporations that practice it. This lack of knowledge is what motivated the study on which this article is based. The key objectives of the study for the article were to determine consumer attitudes towards … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 11 publications
1
13
0
Order By: Relevance
“…Finally, the research proved that there is a significant impact of CSR on brand positioning and brand loyalty. These findings were in line with previous empirical studies Battaglia, et al ( 2014); Dapi and Phiri, (2015); Nagalatha (2015), Lin, (2016) ;Bediako, (2017);Lu, et al, (2020).…”
Section: H022supporting
confidence: 92%
See 1 more Smart Citation
“…Finally, the research proved that there is a significant impact of CSR on brand positioning and brand loyalty. These findings were in line with previous empirical studies Battaglia, et al ( 2014); Dapi and Phiri, (2015); Nagalatha (2015), Lin, (2016) ;Bediako, (2017);Lu, et al, (2020).…”
Section: H022supporting
confidence: 92%
“…It has become the common phenomenon in the present world because of its notable impact on society. Fortune companies across the world spend billions of dollars in fulfilling CSR activities to enhance their reputation and to maintain strong customer relationship management (Dapi and Phiri, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple researchers have shown a link between CSR and positive consumer loyalty with quantitative studies -this is of relevance for marketers because it could improve sales levels and profits. From the findings, Dapi and Agabu Phiri (2015) therefore suggest that corporations take a proactive rather than reactive approach to social and environmental issues. Maignan and Ferrell (2001, p. 13) similarly established a positive relationship between the two, showing "active support for companies committed to cause-related marketing, environmentally friendly practices, or ethics".…”
Section: Consumer Behavior In Relation To Trust Value and Loyaltymentioning
confidence: 90%
“…Results from Maignan and Ferrell (2004) suggest these different connections are intrinsically bound in social context. However, Dapi and Agabu Phiri (2015) aimed to determine consumer attitudes towards specific CSR programs in their study which surveyed South African telecoms consumers, and overwhelmingly found that consumers expected companies to be socially responsible. Min et al (2012), similarly established that consumers had become expectant of this variable.…”
Section: Socially Responsible Consumersmentioning
confidence: 99%
“…The definition of corporate social responsibility from ISO 26000 standard [63] is quite conclusive: "The responsibility of an organisation for the impacts of its decisions and activities on society and the environment, resulting in ethical behaviour and transparency which contributes to sustainable development, including the health and well-being of society; taken into account the expectations of stakeholders; complies with current laws and is consistent with international standards of behaviour; and is integrated throughout the organisation and implemented in its relations." A set of facts that significantly confirm the strong and positive link between corporate social responsibility and customer loyalty, regardless the branch and business, was brought by [64][65][66][67].…”
Section: Literature Review Related To Customer Loyalty Measurement (Wmentioning
confidence: 91%